Penerapan Arsitektur High Tech pada Perancangan Akademi Sepak Bola di Kota Makassar - Ramadhan, Nurihsan; Alfiah, Alfiah; Sutrisno, Mohammad (TIMPALAJA : Architecture Student Journals, 2023)
Abstract_ The Football Academy is a forum that was built with the aim of teaching and nurturing young players to develop so as to give birth to players who have good technical quality and are equipped with extensive knowledge about football coupled with strong mental and physical support as a football player and of course one day be able to plunge as a professional football player. The design of this Football Academy uses the theme of High Tech Architecture, where its implementation takes advantage of technological developments and uses structural elements that are very dominant with fabricated materials on the exterior and interior, as well as structure and utility elements of the building. The embodiment of the High Tech Architecture image is expected to be able to strengthen the character of the building, which is in harmony with the sport of football, which is a sport that develops with the times and is able to describe the function of the building both in the fields of education and sportsmanship.